Avaliações externas e projetos inovadores em educação: a quem e a que servem? - Mara Regina Lemes De Sordi; Margarida Montejano da Silva; Sandra Cristina Tomaz; Frederico Rodrigues P Leal; Juan Carlos da Silva; Charles Durães Leite (Revista Iberoamericana sobre Calidad, Eficacia y Cambio en Educación, 2016)
This study was constructed from the analysis of projects developed in five municipal public education networks in the State of São Paulo, Brazil, that were awarded by the federal Government, through the Laboratório de Experiências Inovadoras em Gestão Educacional as innovative experiences. The investigation involves the participation of educational coordinators of educational units that were instigated, through a questionnaire, to demonstrate on the decisions that they take from the dissemination of the results of students ' performance in large-scale external evaluations. Is structured in the description of the survey and characteristics of federal award for innovation in educational management and goes searching for unfold the representations of the pedagogical coordinators on the use of the data by the professionals of the educational unit in its pedagogical do. In continuity, discusses the various effects of large-scale external evaluations and, finally, brings considerations need to continue the debate on relations between public policy on education that use of awards and the impact of that policy on the improvement of the public school.